Fractionation of Hemp Hurds by Organosolv Pretreatment and its Effect on Production of Lignin and Sugars. Issue 7 (17th April 2014) - Gandolfi, Stefano; Ottolina, Gianluca; Consonni, Roberto; Riva, Sergio; Patel, Ilabahen
Abstract Fractionation of hemp hurds into its three main components, cellulose, hemicellulose, and lignin, was carried out using organosolv pretreatment. The effect of processing parameters, such as temperature, catalyst concentration, reaction time, and methanol (MeOH) concentration, on the dissolution and recovery of hemicellulose and lignin was determined. More than 75 % of total hemicellulose and 75 % of total lignin was removed in a single step with low amounts of degradation products under the following conditions: 165 °C, 3 % H2SO4, 20 min reaction time, and 45 % MeOH. Enzymatic hydrolysis of the residual pretreated biomass yielded up to 60 % of cellulose‐to‐glucose conversion. The maximum recovery of the main components was obtained at a combined severity factor value of around one. Characterization of pretreated biomass and isolated lignin was carried out with FTIR and 2D 13C–1H correlation HSQC NMR spectroscopy, the latter technique providing detailed structural information about the obtained methanol organosolv lignin (MOSL). Results suggested that xylopyranoside is the major carbohydrate associated with hemp lignin. The chemical properties of MOSL samples in terms of their phenolic group content and antioxidant capacity were also investigated. The results showed that MOSL samples have a high phenolic group content and antioxidant capacity relative to Klason lignin.